Pencegahan dan Pengendalian Wabah Penyakit Campak di Kecamatan Ciputat Tangerang Selatan Tahun 2025 - Irviana, Fitriyati; Saptarani, Yanna Dwi (Prisani Cendekia, 2026)
Measles remains a significant public health concern in Indonesia, particularly in densely populated urban areas where disease transmission can occur rapidly. Declining immunization coverage and limited public awareness contribute to the risk of measles outbreaks at the community level. This community service program aimed to improve public knowledge and awareness regarding the prevention and control of measles outbreaks in Ciputat District in 2025. The program employed an educational, promotive, and preventive approach through health education sessions, interactive discussions, and the distribution of educational media in the form of leaflets and posters. The target participants included community members, health cadres, and local community leaders. The results of the program indicated an improvement in participants’ understanding of measles, including its modes of transmission, early symptoms, potential complications, and the importance of immunization as the primary preventive measure. Active participation during discussions reflected increased awareness and positive attitudes toward preventive health behaviors. The involvement of health cadres and community leaders strengthened the dissemination of health information and supported the sustainability of the program outcomes. Overall, this community service activity contributed to enhancing community capacity in preventing and controlling measles outbreaks. The program is expected to support public health efforts in reducing the risk of measles transmission and promoting sustained preventive behaviors at the community level.